Direct evidence of bradycardic effect of omega-3 fatty acids acting on nucleus ambiguus. (14th September 2020) - Barr, Jeffrey L.; Lindenau, Kristen L.; Brailoiu, Eugen; Brailoiu, G. Cristina
Highlights: Omega 3 fatty acids reduce heart rate via unclear mechanisms. Docosahexaenoic acid (DHA) increases cytosolic Ca 2+ and depolarizes nucleus ambiguus. Microinjection of DHA into ambiguus produces bradycardia in conscious rats. DHA modulates cardiac vagal tone by activating FFA1 receptor in nucleus ambiguus. Abstract: Docosahexaenoic acid (DHA) an omega-3 polyunsaturated fatty acid, is an agonist of FFA1 receptor. DHA administration reduces the heart rate via unclear mechanisms. We examined the effect of DHA on neurons of nucleus ambiguus that provide the parasympathetic control of heart rate. DHA produced a dose-dependent increase in cytosolic Ca 2+ concentration in cardiac-projecting nucleus ambiguus neurons; the effect was prevented by GW1100, a FFA1 receptor antagonist. DHA depolarized cultured nucleus ambiguus neurons via FFA1 activation. Bilateral microinjection of DHA into nucleus ambiguus produced bradycardia in conscious rats. Our results indicate that DHA decreases heart rate by activation of FFA1 receptor on cardiac-projecting nucleus ambiguus neurons.